Two-step controlled fermentation using nisin z-producing Lactococcus lactis ssp. lactis and selected strains of the genus Lactiplantibacillus spp. - Sosa, Franco Matías (2024)
Spontaneous fermentation of Brassica vegetables is an ancient method that improves the foods' sensory properties, safety, and shelf life. However, in recent years, there has been a growing interest in studying controlled fermentation with lactic acid bacteria selected based on their technological properties. This study reported the inhibitory activity of a Lactococcus lactis ssp. lactis of marine origin and the evolution of a two-step controlled fermentation using the cited strain and two selected Lactiplantibacillus strains. Lc. lactis ssp. lactis was studied by phenotypic and genotypic methods. The inhibitory activity was assayed against common contaminants and pathogens. The strain behaviour in Chinese cabbage and white cabbage fermentation was studied by monitoring the cell count and inhibitory activity against Listeria innocua ATCC 33090. The two-step controlled fermentation of Chinese and white cabbage was conducted using, in the first step, the Lactococcus strain and, in the second step, the two Lactiplantibacillus strains. The evolution of the processes was monitored by cell counts and pH measurements. PCR amplification confirmed the presence of nisin Z gen in the Lc. lactis ssp. lactis strain. The bacteriocin exerted inhibitory activity against Gram-positive related species but not against Gram-negative ones. The results obtained in the controlled fermentation suggested that the combination of the selected strains is compatible and may improve the fermented matrices' safety.